Exploring Family Resilience Within Adolescent Marriages: A Case Study - siti nurhidayati; Endang Koni Suryaningsih; Deandra Sherly Anantya Fajri (Jurnal Ilmiah Kesehatan)
The prevalence of marriages involving women aged 18 is significant, with approximately 15 million cases globally and over 1.2 million in Indonesia. Early marriage poses a substantial risk of Domestic Violence (DV). This research used a qualitative descriptive design; the research informants were five people who underwent early marriage, and the sample selection used snowball sampling. Data were collected using interviews with an interview guide, and the data collected was subjected to thematic analysis using Nvivo 12 Plus computer software. In this study, five teenagers were married, one woman had never been married, two women were divorced, and two women were married. Two major themes were found in the experience of marriage at an early age, namely internal factors and external factors regarding the resilience of early marriage. In the theme and sub-theme project map, it was found that internal factors include communication patterns with conditions of emotional instability at a young age and behavior patterns that tend to involve partners and even domestic violence. External factors consist of socioeconomic factors, environmental factors, and psychological resilience. The resilience of teenage marriages that needs to be considered is the pattern of effective communication between partners to understand each other and external factors on the psychological resilience of family conflict management. It is hoped that teenagers can limit their social freedom and prepare for marriage well physically, psychologically, and economically.